Direct antiviral agent treatment leads to rapid and significant fibrosis regression after HCV eradication. Issue 9 (20th June 2021) - Kang, Qian; Xu, Jinghang; Luo, Hao; Tan, Ning; Chen, Hongyu; Cheng, Ran; Pan, Jiali; Han, Yifan; Yang, Yuqing; Liu, Dan; Xi, Hongli; Yu, Min; et al.
Abstract: Limited data are currently available regarding fibrosis progression after hepatitis C virus (HCV) eradication. The goal of the present study was to evaluate the effects of HCV eradication on liver stiffness measurements (LSMs), aspartate aminotransferase/platelet ratio index (APRI) scores, fibrosis‐4(FIB‐4) scores, chitinase‐3‐like protein 1 (CHI3L1) levels and Golgi protein 73 (GP73) levels in patients with chronic hepatitis C (CHC). One hundred and two patients who received direct antiviral agents (DAAs) therapy at Peking University First Hospital participated in the present study. Clinical information and serum samples were collected at baseline, at the end of treatment (EOT), and at the weeks 12, 24 and 48 after treatment (W12, W24 and W48, respectively). Of the 102 patients, 51 had mild‐to‐moderate fibrosis (F1/F2), and 51 had advanced fibrosis (F3/F4). The LSMs improved for all patients at the EOT, with observed changes of 2.85 kPa, and the decrease continued to W12. However, a more pronounced improvement was noted for the advanced fibrosis (F3/F4) patients, with a change of 3.6 kPa from baseline to the EOT. Significant decreases between the baseline and EOT measurements were observed in the APRI and FIB‐4 scores [0.64 (0.39–1.21) vs. 0.35 (0.26–0.52), p <0.001; 2.53 (1.30–3.91) vs. 1.87 (0.89–2.5), p <0.001], after which the values decreased until W12, with no significant difference observed. Serum CHI3L1 and GP73 levels were profoundly decreased at the EOT compared with those at baseline [134.07 (154.49) vs. 103.75 (98.04), p =0.025; 98.24 (64.76) vs. 88.91 (50.89), p =0.002]. DAA treatments could significantly improve liver fibrosis of CHC patients as evidenced by decreased liver stiffness, APRI scores and FIB‐4 scores. Improvements in liver fibrosis markers (especially serum CHI3L1 and GP73) were prominent in patients with advanced fibrosis, indicating that serum CHI3L1 and GP73 could be noninvasive markers for monitoring fibrosis in CHC patients. Significance Statement The prospective cohort evaluated the effect of direct antiviral agents (DAAs) on fibrosis regression after hepatitis C virus (HCV) eradication of Chinese people in the real‐world study. This study highlighted that rapid and significant fibrosis regression rather than reduction in inflammation was achieved with DAA treatment, and this regression could be detected as early as the end of treatment. We found the serum CHI3L1 and GP73 levels can be used to monitor changes in fibrosis in CHC patients.